Bio-degradable smart nanocomposite fiber from Moringa oleifera fiber reinforced with safely functionalized carbon nanotubes - Md Abul Kalam; Salvin Mustakim; Mohammad Jellur Rahman; Md Tushar Uddin; Md Ashraful Alam; Mohammad Mahbubur Rahman (AIP Advances)
In this work, we present an innovative approach to fabricating biodegradable smart nanocomposite fibers by incorporating functionalized carbon nanotubes (f-CNTs) onto the surface of Moringa oleifera fibers (MOFs) by using a simple dipping–drying technique. The objective of this research is to enhance the thermal, mechanical, and electrical properties of MOFs through a scalable, non-destructive modification process, making them suitable for advanced applications. A facile radio frequency oxygen plasma processing method is employed to modify CNTs with hydrophilic oxygen-containing groups. The fibers are treated with an alkaline solution coupled with plasma treatment to enhance the interaction between the fiber and the matrices. The performance of the fiber is evaluated by measuring the surface morphology, structural, thermal, mechanical, and electrical properties of the uncoated and f-CNTs-coated fibers. Field emission scanning electron microscope micrographs show that CNTs are uniformly integrated onto the surfaces of the treated MOFs. The results also indicate that interaction between the treated MOFs and f-CNTs, thermal stability, flame retardancy, crystallinity, and mechanical strength of the fibers are increased remarkably with the incorporation of f-CNTs. The resistance per meter of the f-CNTs/treated MOFs fiber drops dramatically from 1.5 MΩ to 13 Ω with the addition of f-CNTs. The current density of the sample increases by about 1000 times, and conductivity rises to 80 S m−1 under the applied voltage of 50 V, which also increases with temperature, indicating the semiconducting nature of CNTs. Therefore, these fibers are suitable for use in various electrical and electronic devices as well as conductive fillers in composite technologies.